Unveiling optimal urban nature for community wellbeing: finding vital key indicators from preceding urban studies - Hassan, Mohammad Mujaheed; Tedong, Peter Aning; Mohd Khir, Azlina; Shari, Zalina; Ponrahono, Zakiah; Sharifudin, Muhammad Phaizal (Human Resource Management Academic Research Society, 2023)
The rapid pace of urbanization highlights the imperative of incorporating nature into cities to address well-being, sustainability, and resilience challenges. This study investigates urban nature, encompassing forests, wetlands, and recreational areas, uncovering their positive effects on urban well-being and resilience, substantiated by scientific research. Notably, urban green spaces such as parks are pivotal in reducing stress, enhancing cognitive, and fostering social cohesion. Ensuring equal access to these spaces is crucial for resident well-being. Urban forests, often underrated, regulate temperature, mitigate noise, and enhance emotional well-being, contributing to climate adaptation and comfort. Wetlands are vital connectors between aquatic and terrestrial ecosystems, impacting water supply, stormwater management, and pollution reduction while acting as reservoirs and natural cleaners. Recreational areas offer opportunities for relaxation and interaction, necessitating customized planning. This research underscores urban nature's significance in shaping livable, sustainable, and resilient cities. Scientific studies stress their contributions to human well-being and the environment, advocating integration, and preservation. A synthesis of science, urban planning, and community engagement establishes the groundwork for nurturing these resources and harmonizing urban living with nature. Embracing urban nature remains essential for a resilient urban future.